2022
DOI: 10.2147/dmso.s386773
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Evaluation of Pregnancy Outcomes Following Bariatric Surgery: A Single-Center Experience

Abstract: Background Bariatric and metabolic surgery (BMS) is an effective treatment for obesity and its complications, but its effect on pregnancy outcomes is inconclusive. The present study aimed to investigate women’s pregnancy status and outcomes as well as the impact of pregnancy intervals after BMS. Methods The menstrual cycle and fertility status of women who underwent BMS in our centre between July 2010 and January 2021 were retrospectively analyzed and followed up until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…We found that anemia is the most common disorder during pregnancy (76.8%). These results were consistent with those published by Wang X et al, which stated that anemia is the most common disorder among pregnant women [ 26 ]. Based on a recent systematic review, anemia is highly expected to occur after BS, with a prevalence of 17-77% of pregnancies [ 29 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We found that anemia is the most common disorder during pregnancy (76.8%). These results were consistent with those published by Wang X et al, which stated that anemia is the most common disorder among pregnant women [ 26 ]. Based on a recent systematic review, anemia is highly expected to occur after BS, with a prevalence of 17-77% of pregnancies [ 29 ].…”
Section: Discussionsupporting
confidence: 94%
“…However, since plasma volume expands faster than red cell mass throughout pregnancy, the high prevalence of anemia may be explained by the fact that hemoglobin concentration is anticipated to be at its lowest month by month [ 30 ]. Accordingly, to prevent and manage anemia during pregnancy, the guidelines suggest that nutritional supplementation be optimized three to six months before conception and that iron, ferritin, and transferrin levels be frequently checked [ 26 ]. GDM refers to DM that is first identified during the second or third trimester of pregnancy and is not immediately identifiable as type 1 or type 2 DM [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Solaiman et al in a group of 158 pregnant patients after BS indicated that there was a negative relationship between shorter TTC interval and GWG (p = 0.002) and lower birth weight and inadequate GWG (p = 0.03); however, the study showed no significant correlation between TTC and PIH, and GDM and neonatal outcomes [26]. In a recent Chinese study, Wang et al found that the spontaneous abortion rate was higher when TTC was lower than 2 years, compared to a TTC interval of 2 years and more (p = 0.04) [29].…”
Section: Optimum Time-to-conception Interval After Bariatric Surgerymentioning
confidence: 88%
“…Considering the major increase in bariatric surgeries in the last decades [16], and given the negative impact of obesity on pregnancy, it is unsurprising that pre-pregnancy bariatric surgeries are a growing field of interest regarding the possible effects on pregnancy outcomes [17]. Several studies have examined pregnancy outcomes following bariatric surgery and have demonstrated a reduced incidence of gestational diabetes, hypertensive disorders, preeclampsia, and LGA infants [18][19][20][21]. Despite these benefits, bariatric surgery can result in nutritional deficiencies, such as deficiencies in folate, iron, vitamin D, which may have maternal and fetal implications.…”
Section: Introductionmentioning
confidence: 99%